Slow Recovery from Inactivation of Na(+) Channels Underlies the Activity-Dependent Attenuation of Dendritic Action Potentials in Hippocampal CA1 Pyramidal Neurons - Colbert, Costa M. (J Neurosci, 1997)
Na(+) action potentials propagate into the dendrites of pyramidal neurons driving an influx of Ca(2+) that seems to be important for associative synaptic plasticity. During repetitive (10–50 Hz) firing, dendritic action potentials display a marked and prolonged voltage-dependent decrease in amplitude. Such a decrease is not apparent in somatic action potentials. We investigated the mechanisms of the different activity dependence of somatic and dendritic action potentials in CA1 pyramidal neurons of adult rats using whole-cell and cell-attached patch-clamp methods. There were three main findings. First, dendritic Na(+) currents decreased in amplitude when repeatedly activated by brief (2 msec) depolarizations. Recovery was slow and voltage-dependent. Second, Na(+) currents decreased much less in somatic than in dendritic patches. Third, although K(+) currents remained constant during trains, K(+) currents were necessary for dendritic action potential amplitude to decrease in whole-cell experiments. These results suggest that regional differences in Na(+) and K(+) channels determine the differences in the activity dependence of somatic and dendritic action potential amplitudes.